A fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation and a preparation method thereof

By introducing micro-nanocarbon on the surface of the fiber felt and strengthening it in concert with SiOC aerogel, the problem of insufficient strength of SiOC aerogel is solved, and the high temperature stability, oxidation resistance and heat insulation are improved. It is suitable for high-speed aircraft oxidation and ablation resistance needs.

CN118851770BActive Publication Date: 2025-01-10HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410893855.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-01-10
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

Due to the poor strength in high-speed aircraft, existing SiOC aerogel materials are difficult to meet the needs of high-temperature stable, low thermal conductivity, and high-strength integrated lightweight anti-insulation/thermal insulation materials, especially in oxidative ablation and aerodynamic erosion environments. good.

Method used

By introducing micro-nanocarbon on the fiber surface of the fiber felt, the modified fiber felt is formed and strengthened in concert with the SiOC aerogel matrix, the multi-step curing and carbonization process of phenolic resin and silicone precursor are used to realize the fiber felt. and uniform distribution and strengthening of micro-nanocarbons.

Benefits of technology

Improve the high temperature stability, oxidation resistance and strength of the composite material, making it both lightweight, high strength, good oxidation resistance and thermal insulation properties, low density, low thermal conductivity and exhibit high temperature environment Excellent oxidation and ablation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851770B_ABST
    Figure CN118851770B_ABST
Patent Text Reader

Abstract

The present invention provides an oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material and a preparation method thereof, belonging to the technical field of thermal protection of fiber-reinforced aerogel composite materials, wherein the composite material comprises a modified fiber felt reinforcement and a SiOC aerogel matrix; the modified fiber felt reinforcement is a fiber felt with micro-nano carbon coated on the fiber surface. In the modified fiber felt reinforcement of the oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material provided by the present invention, the continuous fiber felt and the heterogeneous micro-nano carbon synergistically enhance the strength of the SiOC aerogel matrix, while the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon, thereby achieving a common improvement in the high-temperature stability, oxidation resistance and strength of the composite material, so that the composite material has both light weight, high strength and good oxidation resistance and thermal insulation properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal protection of fiber-reinforced aerogel composite materials, and in particular to an oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material and a preparation method thereof. Background Art

[0002] High-speed aircraft thermal protection materials face extreme service environments of long-term high temperature, oxidation ablation and aerodynamic erosion. In order to ensure the safety of aircraft, it is urgent to carry out research on the next generation of high-temperature stable, low thermal conductivity, high-strength integrated lightweight protection / insulation materials. SiOC aerogel has attracted widespread attention due to its excellent oxidation resistance, high porosity and low thermal conductivity, but the poor strength of SiOC aerogel limits its further application. Summary of the invention

[0003] In view of one or more technical problems existing in the prior art, the present invention provides an oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material and a preparation method thereof. The continuous fiber felt and heterogeneous micro-nano carbon in the modified fiber felt reinforcement of the oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material provided by the present invention synergistically enhance the strength of the SiOC aerogel matrix. At the same time, the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon, thereby achieving a joint improvement in the high-temperature stability, oxidation resistance and strength of the composite material, so that the composite material has both light weight, high strength and good oxidation resistance and thermal insulation properties.

[0004] In a first aspect, the present invention provides an oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material, the composite material comprising a modified fiber felt reinforcement and a SiOC aerogel matrix; the modified fiber felt reinforcement is a fiber felt with micro-nano carbon coated on the fiber surface.

[0005] Preferably, the fiber felt is one or more of quartz fiber felt, mullite fiber felt, alumina fiber felt, zirconia fiber felt, and silicon carbide fiber felt.

[0006] In a second aspect, the present invention provides a method for preparing the oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material according to the first aspect, the preparation method comprising the following steps:

[0007] S1. The fiber felt is immersed in a phenolic resin solution, and then filtered, first cured, and first carbonized to obtain a modified fiber felt;

[0008] S2. The modified fiber felt is immersed in a siloxane precursor solution, and then subjected to a second curing and a second carbonization; the siloxane precursor solution is a mixture comprising a siloxane precursor, a second solvent, water and a catalyst;

[0009] S3. Repeat step S2 to obtain a fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation.

[0010] Preferably, the phenolic resin solution is a mixture comprising a phenolic resin and a first solvent;

[0011] Preferably, the first solvent is at least one of an alcohol substance and water, preferably at least one of ethanol, isopropanol, ethylene glycol and water.

[0012] Preferably, the concentration of the phenolic resin solution is 10-40 wt %.

[0013] Preferably, the first curing temperature is 90-180°C and the time is 1-6 hours; and / or

[0014] The temperature of the first carbonization is 500-800° C., and the time is 1-6 hours.

[0015] Preferably, the mass ratio of the siloxane precursor to the second solvent is 1:2-5;

[0016] Preferably, the siloxane precursor comprises at least a trifunctional silane, preferably at least one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and (3-glycidoxy)propyltrimethoxysilane;

[0017] Preferably, the second solvent is at least one of ethanol, isopropanol, acetone and water.

[0018] Preferably, the mass ratio of the siloxane precursor to water is 1:0.5-1.

[0019] Preferably, the mass ratio of the siloxane precursor to the catalyst is 1:0.1-1;

[0020] Preferably, the catalyst is an alkaline catalyst, preferably aqueous ammonia.

[0021] Preferably, the second curing temperature is 60-90°C and the time is 12-24h; and / or

[0022] The temperature of the second carbonization is 500-800° C., and the time is 1-6 hours.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The present invention introduces micro-nano carbon on the surface of the fiber of the continuous fiber felt to enhance and modify the fiber felt, which plays a role in reinforcing the fiber felt without significantly increasing the density of the fiber felt, thereby obtaining a modified fiber felt reinforcement. The continuous fiber felt and heterogeneous micro-nano carbon in the modified fiber felt reinforcement synergistically enhance the strength of the SiOC aerogel matrix, while the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon. The mutual reinforcement of the continuous fiber felt, heterogeneous micro-nano carbon and SiOC aerogel matrix achieves a common improvement in the high-temperature stability, oxidation resistance and strength of the composite material, so that the composite material has both light weight, high strength and good oxidation resistance and thermal insulation properties.

[0025] The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation provided by the present invention has a low density (0.26-0.33 g / cm 3 ), high strength (5% strain compressive strength is not less than 0.4MPa, and can reach up to 0.9MPa), excellent thermal insulation (room temperature thermal conductivity <0.04W / (m·K)) and oxidation resistance (after long-term high temperature (500℃ / 10h) test in air environment, the mass loss rate is <4%), and has excellent comprehensive performance.

[0026] The present invention first impregnates the fiber felt with a phenolic resin solution and guides the phenolic resin solution to be evenly distributed on the fiber surface under the action of surface tension by suction filtration, thereby achieving weight loss. Then, after curing and carbonization, the micro-nano carbon is generated in situ on the fiber surface by using the in-situ carbonization strategy of the phenolic resin, which can not only realize the uniform introduction of micro-nano carbon into the fiber felt, but also play a role in strengthening the fiber felt without significantly increasing the density of the fiber felt, thereby solving the problem of the difficulty in uniformly introducing solid powder into the continuous fiber felt in the prior art. Finally, the modified fiber felt is compounded with SiOC aerogel to improve the strength of the SiOC aerogel matrix, thereby overcoming the problem of poor strength of the existing SiOC aerogel. At the same time, the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon on the fiber surface in the continuous fiber felt, so that the composite material has both light weight, high strength, good oxidation resistance and thermal insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a preparation flow chart of a fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation provided by the present invention;

[0029] Figure 2 The compressive stress-strain curves (above) and the 5% strain compressive strength bar graph (below) of the SiOC aerogel composite materials provided in Examples 1-4 of the present invention and Comparative Example 1;

[0030] Figure 3 is a bar graph of room temperature thermal conductivity of the SiOC aerogel composite materials provided in Examples 1-4 of the present invention and Comparative Example 1;

[0031] Figure 4 It is a bar graph of the weight loss rate of the SiOC aerogel composite materials provided in Examples 1-4 of the present invention and Comparative Example 1 when tested in air at 500° C. for 10 hours. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] In a first aspect, the present invention provides an oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material, the composite material comprising a modified fiber felt reinforcement and a SiOC aerogel matrix; the modified fiber felt reinforcement is a fiber felt with micro-nano carbon coated on the fiber surface.

[0034] The present invention introduces micro-nano carbon on the surface of the fiber of the continuous fiber felt to enhance and modify the fiber felt, which plays a role in reinforcing the fiber felt without significantly increasing the density of the fiber felt, thereby obtaining a modified fiber felt reinforcement. The continuous fiber felt and heterogeneous micro-nano carbon in the modified fiber felt reinforcement synergistically enhance the strength of the SiOC aerogel matrix, while the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon. The mutual reinforcement of the continuous fiber felt, heterogeneous micro-nano carbon and SiOC aerogel matrix achieves a common improvement in the high-temperature stability, oxidation resistance and strength of the composite material, so that the composite material has both light weight, high strength and good oxidation resistance and thermal insulation properties.

[0035] The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation provided by the present invention has a low density (0.26-0.33 g / cm 3 ), high strength (5% strain compressive strength is not less than 0.4MPa, and can reach up to 0.9MPa), excellent thermal insulation (room temperature thermal conductivity <0.04W / (m·K)) and oxidation resistance (after long-term high temperature (500℃ / 10h) test in air environment, the mass loss rate is <4%), and has excellent comprehensive performance.

[0036] According to some preferred embodiments, the fiber felt is one or more of quartz fiber felt, mullite fiber felt, alumina fiber felt, zirconia fiber felt, and silicon carbide fiber felt.

[0037] In a second aspect, the present invention provides a method for preparing the oxidation-ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material according to the first aspect, the preparation method comprising the following steps:

[0038] S1. The fiber felt is immersed in a phenolic resin solution, and then filtered, first cured, and first carbonized to obtain a modified fiber felt;

[0039] S2. The modified fiber felt is immersed in a siloxane precursor solution, and then subjected to a second curing and a second carbonization; the siloxane precursor solution is a mixture comprising a siloxane precursor, a second solvent, water and a catalyst;

[0040] S3. Repeat step S2 to obtain a fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation.

[0041] The present invention first impregnates the fiber felt with a phenolic resin solution and guides the phenolic resin solution to be evenly distributed on the fiber surface under the action of surface tension by suction filtration, thereby achieving weight loss. Then, after curing and carbonization, the micro-nano carbon is generated in situ on the fiber surface by using the in-situ carbonization strategy of the phenolic resin, which can not only realize the uniform introduction of micro-nano carbon into the fiber felt, but also play a role in strengthening the fiber felt without significantly increasing the density of the fiber felt, thereby solving the problem of the difficulty in uniformly introducing solid powder into the continuous fiber felt in the prior art. Finally, the modified fiber felt is compounded with SiOC aerogel to improve the strength of the SiOC aerogel matrix, thereby overcoming the problem of poor strength of the existing SiOC aerogel. At the same time, the SiOC aerogel matrix improves the oxidation resistance of the micro-nano carbon on the fiber surface in the continuous fiber felt, so that the composite material has both light weight, high strength, good oxidation resistance and thermal insulation properties.

[0042] According to some preferred embodiments, the phenolic resin solution is a mixture of a phenolic resin and a first solvent; preferably, the first solvent is at least one of an alcohol substance and water, preferably at least one of ethanol, isopropanol, ethylene glycol and water.

[0043] The present invention does not specifically limit the type of phenolic resin, which may be a liquid resin or a solid resin, and is preferably but not limited to at least one of the group consisting of Resinova LBR 200, Dynea LRF 3340, Borden Resin 7323, and Borden Resin 7323.

[0044] According to some preferred embodiments, the concentration of the phenolic resin solution is 10 to 40 wt% (for example, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt% or 40 wt%). The present invention controls the concentration of the phenolic resin solution within the above range to ensure that the generated micro-nano carbon is evenly coated on the fiber surface to enhance the fiber felt. If the concentration of the phenolic resin solution is too low, the reinforcing effect on the fiber felt is not obvious; if the concentration of the phenolic resin solution is too high, the fluidity of the phenolic resin solution is poor, it cannot be fully impregnated, and the processing performance is poor.

[0045] According to some preferred embodiments, the first curing temperature is 90-180°C (for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C), and the time is 1-6h (for example, 1h, 2h, 3h, 4h, 5h or 6h); and / or

[0046] The first carbonization temperature is 500-800°C (for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C), and the time is 1-6h (for example, 1h, 2h, 3h, 4h, 5h or 6h).

[0047] According to some preferred embodiments, the mass ratio of the siloxane precursor to the second solvent is 1:2-5;

[0048] Preferably, the siloxane precursor includes at least a trifunctional silane, preferably at least one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and (3-epoxypropyloxy)propyltrimethoxysilane; the siloxane precursor of the present invention includes at least a trifunctional silane to ensure cross-linking to obtain a three-dimensional structure.

[0049] Preferably, the second solvent is at least one of ethanol, isopropanol, acetone and water.

[0050] According to some preferred embodiments, the mass ratio of the siloxane precursor to water is 1:0.5-1 (for example, it can be 1:1, 1.2:1, 1.4:1, 1.5:1, 1.6:1, 1.8:1 or 2:1).

[0051] According to some preferred embodiments, the mass ratio of the siloxane precursor to the catalyst is 1:0.1 to 1 (for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1);

[0052] Preferably, the catalyst is an alkaline catalyst, preferably aqueous ammonia. The mass fraction of aqueous ammonia in the present invention is preferably 28%.

[0053] The present invention controls the gelation rate and the degree of crosslinking by regulating the amount of the catalyst within the above range. The inventors have found that if the amount of the catalyst is too large, the gelation rate will be too fast, the degree of crosslinking will be insufficient, and the structure of the prepared SiOC aerogel will be loose and the strength will be insufficient; if the amount of the catalyst is too small, the gelation rate will be too slow, the structure of the prepared SiOC aerogel will be too dense, and the porosity will be low.

[0054] According to some preferred embodiments, the second curing temperature is 60-90°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C), and the time is 12-24h (for example, 12h, 14h, 16h, 18h, 20h, 22h or 24h).

[0055] According to some preferred embodiments, the second carbonization temperature is 500-800°C (for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C), and the time is 1-6h (for example, 1h, 2h, 3h, 4h, 5h or 6h).

[0056] According to some preferred embodiments, in S2, the impregnation is vacuum impregnation, and the pressure of the vacuum impregnation is preferably -0.07 to -0.06 MPa. The inventors found that if the negative pressure is too high, the second solvent is easily volatilized, which is not conducive to the impregnation of the siloxane precursor solution; if the negative pressure is too low, the gas in the modified fiber felt cannot be discharged, and the modified fiber felt cannot be fully impregnated with the siloxane precursor solution, which is not conducive to the uniform distribution of the SiOC aerogel.

[0057] According to some preferred embodiments, in S3, step S2 is repeated once. The present invention further improves the strength of the composite material by repeating step S2. The inventors found that if step S2 is not repeated, the strength of the composite material is low; if the number of repetitions is too many, the density and room temperature thermal conductivity of the composite material will increase.

[0058] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0059] Example 1

[0060] S1. Preparation of modified fiber felt: immerse continuous quartz fiber felt in a phenolic resin solution with a concentration of 10wt% for 2h, wherein the phenolic resin solution is obtained by mixing phenolic resin and ethylene glycol, and then remove most of the solvent in the pores of the quartz fiber felt by filtration, and then put it into a 150℃ oven for curing for 3h, and finally put it into a carbonization furnace, heat it to 800℃, and keep it for 2h, so that micro-nano-sized carbon is generated in situ in the phenolic resin on the fiber surface to obtain a modified fiber felt.

[0061] S2. Dissolve methyltrimethoxysilane and dimethyldiethoxysilane in a mixed solution of ethanol and water, hydrolyze for 30 minutes, then add ammonia water as a catalyst and mix well to obtain a siloxane precursor solution, wherein the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:1.5. Impregnate the modified fiber felt with the siloxane precursor solution, control the impregnation pressure at -0.07MPa, maintain for 30 minutes, then place it in a 70°C oven for curing for 12 hours, then take it out and dry it for 12 hours, and finally place it in a carbonization furnace, heat it to 800°C, and maintain it for 2 hours.

[0062] S3. Repeat step S2 once to obtain a fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation.

[0063] Example 2

[0064] It is basically the same as Example 1, except that in S1, the concentration of the phenolic resin solution is 10 wt %.

[0065] Example 3

[0066] It is basically the same as Example 1, except that in S1, the concentration of the phenolic resin solution is 30 wt%.

[0067] Example 4

[0068] It is basically the same as Example 1, except that in S1, the concentration of the phenolic resin solution is 40 wt%.

[0069] Example 5

[0070] It is basically the same as Example 3, except that in S2, in the siloxane precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:0.5.

[0071] Example 6

[0072] It is basically the same as Example 3, except that in S2, in the siloxane precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:1.

[0073] Example 7

[0074] It is basically the same as Example 3, except that in S2, in the siloxane precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:3.

[0075] Example 8

[0076] It is basically the same as Example 3, except that in S2, in the siloxane precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:5.

[0077] Comparative Example 1

[0078] It is basically the same as Example 1, except that the fiber felt is not modified, that is, there is no step S1.

[0079] Comparative Example 2

[0080] It is basically the same as Example 1, except that in S1, the concentration of the phenolic resin solution is 5 wt %.

[0081] Comparative Example 3

[0082] It is basically the same as Example 1, except that there is no step S3.

[0083] Comparative Example 4

[0084] It is basically the same as Example 3, except that in S2, in the siloxane precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water is 4:1:12:3:6.

[0085] The ammonia content is too high, the silane reactive solution gels too quickly, and there is no operating time window for impregnating the fiber felt.

[0086] The preparation parameters and performance comparison of the composite materials of the embodiments of the present invention and the comparative examples are shown in Table 1.

[0087] Table 1. Comparison of preparation parameters and properties of composite materials in the examples of the present invention and the comparative examples

[0088]

[0089]

[0090] The method for testing the above performance of the present invention is as follows:

[0091] Compression performance: refer to GB / T1448-2005 "Test method for compression performance of fiber reinforced plastics";

[0092] Thermal conductivity: According to GB / T32064-2015, the thermal conductivity of the sample was measured using a thermal constant analyzer model TPS3500 produced by HotDisk of Sweden;

[0093] Weight loss rate: The prepared composite material was placed in a 500°C muffle furnace, heated to 500°C, and kept at this temperature for 10 hours before calculating the weight loss rate;

[0094] Density: First, process the composite material into a rectangular block, measure its mass and dimensions, and then calculate the volume and density.

[0095] It should be noted that the ratio of siloxane precursor solution in Table 1 refers to the mass ratio of methyltrimethoxysilane, dimethyldiethoxysilane, ethanol, water and ammonia water. It can be seen from the results of Table 1 that the present invention generates micro-nano carbon on the fiber surface through the in-situ carbonization strategy of phenolic reinforced quartz fiber felt, and prepares a SiOC aerogel composite material synergistically reinforced with continuous fibers and micro-nano carbon. The composite material has excellent comprehensive properties of light weight, low thermal conductivity, low strain and high strength, and the weight loss rate is less than 4% after being tested at 500°C in air for 10 hours, which proves that the material has excellent antioxidant properties. By comparing Example 1 with Comparative Example 1, it can be seen that the present invention adopts an in-situ carbonization strategy to introduce micro-nano carbon on the fiber surface of the fiber felt, which can significantly improve the compressive strength of the composite material, and at the same time has no obvious effect on the density and room temperature thermal conductivity of the composite material, while achieving the improvement of the strength of the composite material while ensuring the light weight and thermal insulation properties of the composite material.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation, characterized in that: The composite material comprises a modified fiber felt reinforcement and a SiOC aerogel matrix; the modified fiber felt reinforcement is a fiber felt with micro-nano carbon coated on the fiber surface; The method for preparing the oxidation-resistant and ablation-resistant fiber / carbon synergistically reinforced SiOC aerogel composite material comprises the following steps: S1. The fiber felt is immersed in a phenolic resin solution, and then filtered, first cured, and first carbonized to obtain a modified fiber felt; S2. The modified fiber felt is immersed in a siloxane precursor solution, and then subjected to a second curing and a second carbonization; the siloxane precursor solution is a mixture comprising a siloxane precursor, a second solvent, water and a catalyst; S3. Repeat step S2 to obtain a fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation; The concentration of the phenolic resin solution is 10-40wt%; The first curing temperature is 90-180°C and the time is 1-6 hours; The first carbonization temperature is 500-800°C and the time is 1-6h; The siloxane precursor is at least one of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and (3-glycidoxy)propyltrimethoxysilane; The second curing temperature is 60-90°C and the time is 12-24h; The temperature of the second carbonization is 500-800° C., and the time is 1-6 hours.

2. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 1, characterized in that: The fiber felt is one or more of quartz fiber felt, mullite fiber felt, alumina fiber felt, zirconia fiber felt, and silicon carbide fiber felt.

3. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 1, characterized in that: The phenolic resin solution is a mixture of a phenolic resin and a first solvent.

4. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 3, characterized in that: The first solvent is at least one of an alcohol substance and water.

5. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 4, characterized in that: The first solvent is at least one of ethanol, isopropanol and ethylene glycol.

6. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 1, characterized in that: The mass ratio of the siloxane precursor to the second solvent is 1:2-5.

7. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 6, characterized in that: The second solvent is at least one of ethanol, isopropanol and acetone.

8. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 1, characterized in that: The mass ratio of the siloxane precursor to water is 1:0.5~1.

9. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 1, characterized in that: The mass ratio of the siloxane precursor to the catalyst is 1:0.1~1.

10. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 9, characterized in that: The catalyst is a basic catalyst.

11. The fiber / carbon synergistically reinforced SiOC aerogel composite material resistant to oxidation and ablation according to claim 10, characterized in that: The catalyst is aqueous ammonia.

Citation Information

Patent Citations

  • Ceramic microsphere-modified carbon fiber preform-reinforced silica carbon-phenolic aldehyde composite material and preparation method thereof

    CN112940445A

  • High-strength aerogel composite material and preparation method thereof

    CN113773044A